Tomography of the Earth's Crust: From Geophysical Sounding to Real-Time Monitoring GEOTECHNOLOGIEN Science Report No. 21 - Weber, Michael; Münch, Ute (Advanced Technologies in Earth Sciences, 2014)
The research work on the topic of ''Tomography of the Earth's Crust: From Geophysical Sounding to Real-Time Monitoring'' has focused on the development of cross-scale multiparameter methods and their technological application together with the development of innovative field techniques. Seismic wave field inversion theory, diffusion and potential methods were developed and optimized with respect to cost and benefit aspects. This volume summarizes the scientific results of nine interdisciplinary joint projects funded by the German Federal Ministry of Education and Research in the framework of the Research and Development Program GEOTECHNOLOGIEN. Highlights and innovations presented cover many length scales and involve targets ranging from applications in the laboratory, to ground water surveys of heterogeneous aquifer, geotechnical applications like tunnel excavation, coal mine and CO2 monitoring and the imaging and monitoring of tectonic and societally relevant objects as active faults and volcanoes. To study these objects, the authors use the full spectrum of geophysical methods (ultrasonics, seismic and seismology, electromagnetics, gravity, and airborne) in combination with new methods like seismic interferometry, diffuse wave field theory and full-wave-form inversion in 3D and partially also in 4D. Geophysical Sounding to Real-Time Monitoring'' has focused on the development of cross-scale multiparameter methods and their technological application together with the development of innovative field techniques. Seismic wave field inversion theory, diffusion and potential methods were developed and optimized with respect to cost and benefit aspects. This volume summarizes the scientific results of nine interdisciplinary joint projects funded by the German Federal Ministry of Education and Research in the framework of the Research and Development Program GEOTECHNOLOGIEN. Highlights and innovations presented cover many length scales and involve targets ranging from applications in the laboratory, to ground water surveys of heterogeneous aquifer, geotechnical applications like tunnel excavation, coal mine and CO2 monitoring and the imaging and monitoring of tectonic and societally relevant objects as active faults and volcanoes. To study these objects, the authors use the full spectrum of geophysical methods (ultrasonics, seismic and seismology, electromagnetics, gravity, and airborne) in combination with new methods like seismic interferometry, diffuse wave field theory and full-wave-form inversion in 3D and partially also in 4D. 2 monitoring and the imaging and monitoring of tectonic and societally relevant objects as active faults and volcanoes. To study these objects, the authors use the full spectrum of geophysical methods (ultrasonics, seismic and seismology, electromagnetics, gravity, and airborne) in combination with new methods like seismic interferometry, diffuse wave field theory and full-wave-form inversion in 3D and partially also in 4D.